Manejo Agronómico del Cultivo de Berenjena (Solanum melongena L.) en el Ecuador - Valero Moreno, Franklin Mauricio (2022)
This paper describes the agronomic management of eggplant (Solanum melongena L.) in Ecuador. The agronomic management of the crop must be accurate and timely to be successfully marketed, otherwise there may be crop losses or decrease in fruit quality, so the cultural work and phytosanitary controls are carried out in a very professional and specialized manner. The conclusions determine that it is necessary to carry out training pruning and tutors in the plantation in order to improve the performance of cultural tasks, to carry out research implementing the agronomic management of the eggplant crop to determine its effect on yield, to promote planting trials of the crop in coastal agricultural areas of Ecuador, since it is a crop that has an optimal development in warm climates. In Ecuador there are few production areas of eggplant, due to the distrust of producers by the little domestic consumption of this vegetable, eggplant production is currently delivered mainly to traders who distribute the eggplant to coastal regions, highlands and east to reach commercial as Supermanxi, Aki, Mi Comisariato, demand a high quality product and defined size, This product is in high demand internationally but has not yet been exploited, so the producer should be encouraged through credit facilities in financial institutions to invest in their crops, as well as analyze the major consumers of this food, as it will open trade channels for a non-traditional product with nutritional qualities very desirable, which will generate sources of employment and national monetary value.